2008
DOI: 10.1021/ie7017228
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Sequestration by Aqueous Red Mud Carbonation at Ambient Pressure and Temperature

Abstract: An analysis of carbonation was carried out with the aqueous fresh red mud suspension at a liquid-to-solid ratio of 10 kg/kg, as well as in the leached-hydrated matrixes and leachates isolated from this red mud suspension after three successive leachings, to evaluate their intrinsic carbonation potential at ambient conditions (temperature of 20 ± 1 °C and atmospheric pressure). The carbonation assays were performed at 20 °C using a CO2 concentration of 15.00 vol% at a flow rate of 5 mL/min. The red mud matrix h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(34 citation statements)
references
References 13 publications
0
33
0
1
Order By: Relevance
“…Carbonation capacity (5.3 g of CO 2 /100 g) of RM II at l/s ratio 0.35 when compared to the results (4.15 g of CO 2 /100 g at l/s ratio 10.0) of other investigator [30], it was found that higher l/s ratio did not yield higher CO 2 capture efficiency. …”
Section: Effect Of Liquid To Solid Ratiomentioning
confidence: 67%
“…Carbonation capacity (5.3 g of CO 2 /100 g) of RM II at l/s ratio 0.35 when compared to the results (4.15 g of CO 2 /100 g at l/s ratio 10.0) of other investigator [30], it was found that higher l/s ratio did not yield higher CO 2 capture efficiency. …”
Section: Effect Of Liquid To Solid Ratiomentioning
confidence: 67%
“…1.0-1.5 t of RM which represents worldwide over 66 million ton. Red mud waste has been investigated for different applications such as production of ceramics [1], recovery of iron [2], production of composites with polymers [3], production of hydrogen [4], as catalyst [5], for the CO 2 sequestration [6] and to produce coagulants [7,8]. Krimpalis et al described the reduction of iron from RM to produce the magnetic phase maghemite ␥-Fe 2 O 3 [9].…”
Section: Introductionmentioning
confidence: 99%
“…Various methods have been used for neutralization of red mud by adding liquid carbon dioxide [12,14], saline brines or seawater [15], Ca and Mg-rich brines, soluble Ca and Mg salts, acidic water from mine tailing, fly ash, carbon dioxide gas [16,17]. The NRM is utilized for environmental benefits.…”
Section: Introductionmentioning
confidence: 99%